Paciente masculino de 60 años con sobrepeso y hemiplejia izquierda - Laje Morante, Mercy Judith (2019)
This paper presents the health and nutritional status of a 60-year-old Ecuadorian adult who is overweight due to a long term of his working life as a driver having bad eating habits that include meals, eating fast and spicy foods, he also referred us that very rarely physical activity and only manageable and came to his home to rest, the patient also presents a state of hemiplegia to the left now it is more difficult to move, as this is the condition of evidence as a paralysis of the East side is the case of a stroke 6 months ago, caused by poor control of hypertension maintained 8 years ago. In addition to this condition, the patient has a dysfunction that makes it difficult and puts at risk their nutritional status and that their diet is not adequate. The present study shows the clinical pathologies of a hypertensive patient, with overweight, left hemiplegia and his dysphagia causing a nutritional risk, that you have a good diet and nutrition, for the occasion. . A nutritional action plan was also developed to improve their nutritional status, in addition to facilitating the process of swallowing and its main complication and primary reason for the patient to go to a nutrition professional.